Pengaruh Opini Audit Tahun Sebelumnya dan Solvabilitas terhadap Opini Audit Going Concern pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Septiana, Gina; Haryadi, Teddy; Fani, Lastri Anggi; Dewi, Mike Kusuma; Meirina, Elsa (Jurnal Informatika Ekonomi Bisnis, 2025)
Going concern is an assumption in accounting that estimates a business entity will continue in the long term and will not be liquidated in the short term. This research aims to analyze the audit opinion going concern through some factors: previous year’s audit opinion and solvability. This research use manufacturing sector companies listed in Indonesia Stock Exchange between 2017 -2023 as the sample. Population of this research is 128 companies. Research sample amounts to 50 companies selected with purpose sampling method, with observation period of 7 years. The method that been used to analysis the correlation between variable are logistic regression method. The results showed that partially, previous year’s audit opinion negatively affecting going-concern audit opinion. While the solvability positive influence on going-concern audit opinion.